The evolution of meaning in life in adolescents (Journal of the College of Basic Education, 2022)
Many researchers, including Eriksson Ramarchia, believe that thinking about the meaning of our lives appears specifically in adolescence, as adolescence is the beginning of identity development, and the evidence for this is that most of the questions of adolescents were about the future, the philosophy of life, and the meaning of life. In addition, it was found that adolescents who do not suffer From psychological problems, they used to talk to adults about infectious topics related to the meaning of life, so the current research aimed to know the meaning of life in adolescents in terms of the difference in this meaning according to the variables of age and gender.